2014
DOI: 10.1038/onc.2014.131
|View full text |Cite
|
Sign up to set email alerts
|

A long noncoding RNA critically regulates Bcr-Abl-mediated cellular transformation by acting as a competitive endogenous RNA

Abstract: Aberrant expression of long noncoding RNAs (lncRNAs) is associated with various human cancers. However, the role of lncRNAs in Bcr-Abl-mediated chronic myeloid leukemia (CML) is unknown. In this study, we performed a comprehensive analysis of lncRNAs in human CML cells using an lncRNA cDNA microarray and identified an lncRNA termed lncRNA-BGL3 that acted as a key regulator of Bcr-Abl-mediated cellular transformation. Notably, we observed that lncRNA-BGL3 was highly induced in response to disruption of Bcr-Abl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(140 citation statements)
references
References 57 publications
2
137
0
1
Order By: Relevance
“…In the past few years, further publications on ceRNAs have extended ceRNA categories into pseudogenes, lncRNAs, circular RNAs (circRNAs), small noncoding RNAs, and even mRNAs (50). For the hematopoietic system, Guo et al reported that lncRNA-BGL3, which regulates Bcr-Abl-mediated chronic myeloid leukemia (CML), acts as a ceRNA to soak up miR-17, miR-20a, miR-20b, miR-93, miR106a, and miR-106b and alleviate their repression of PTEN (52). Here we demonstrated that lnc-MC could interact directly and physically with miR-199a-5p, functioning as a ceRNA to release ACVR1B expression.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, further publications on ceRNAs have extended ceRNA categories into pseudogenes, lncRNAs, circular RNAs (circRNAs), small noncoding RNAs, and even mRNAs (50). For the hematopoietic system, Guo et al reported that lncRNA-BGL3, which regulates Bcr-Abl-mediated chronic myeloid leukemia (CML), acts as a ceRNA to soak up miR-17, miR-20a, miR-20b, miR-93, miR106a, and miR-106b and alleviate their repression of PTEN (52). Here we demonstrated that lnc-MC could interact directly and physically with miR-199a-5p, functioning as a ceRNA to release ACVR1B expression.…”
Section: Discussionmentioning
confidence: 99%
“…The general mechanism by which lncRNAs function is not yet fully understood, but lncRNA-BGL3 was reported to play an important role in BCR-ABL1 transformation. In K562 and primary CML cells, BCR-ABL1 inhibits the expression of this lncRNA in a kinase-dependent manner via the MYC transcription factor [87]. Forced expression of lncRNA-BGL3 in K562 cells induced apoptosis and reduced the ability of these cells to engraft in mice.…”
Section: Crklmentioning
confidence: 99%
“…LncRNA-BGL3 exerted a tumor-suppressing function by serving as a PTEN ceRNA and its expression was repressed by Bcr-Abl through c-Myc-dependent DNA methylation [76]. …”
Section: The Function Of Cernas In Cancermentioning
confidence: 99%